Perubahan Hasil Belajar Materi Energi Dan Perubahannya Melalui Model Pembelajaran Kooperatif Team Games Tournament (TGT) Pada Peserta Didik Kelas IV SD - Afifah Maulida Hermanto; Wati Sukmawati (Postgraduate, University of Mataram, 2025)
The curriculum of elementary education is natural science (IPA) which is a field of study related to natural phenomena systematically. The purpose of learning science courses in elementary schools is to gain understanding and knowledge about interesting science concepts that can be applied in everyday life. This is important to address the problems of lack of teacher creativity, student learning activities, and student learning outcomes. Although relevant, this is a generalization, namely how TGT addresses less than optimal learning outcomes in energy material. involving 41 fourth grade students of Jatinegara Elementary School, East Jakarta, divided into a control class and an experimental class. 22 out of 24 students (91.7%) showed an increase in learning outcomes after participating in Team Games Tournament (TGT)-based learning, while only 2 students experienced a decrease in the control class that did not receive similar treatment, while the rest experienced an increase. The total number of students mentioned in the results (24 experimental students + X control students) is not explicitly 41. You need to make sure the total sample and distribution between the experimental and control classes are clearly and consistently stated in the methods and results sections. If the experimental class only has 24 students, then the control class only has 17 students (41-24), 22 out of 24 students (91.7%) showed an increase in learning outcomes after participating in Team Games Tournament (TGT)-based learning, while only 2 students experienced a decrease in the control class that did not receive similar treatment, while the rest experienced an increase.